Metric invariants of equations of Hermitean quadrics in unitary non-Euclidean and semi- non-Euclidean spaces - Ezhova-Guseva, L.; Klimanova, T.; Yasinskaya, E. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Л. М. Ежова-Гусева, Т. М. Климанова, Е. У. Ясинская. Метрические инварианты эрмитовых квадрик в унитарных неевклидовых и полунеевклндовых пространствах L. Ježova-Guseva, T. Klimanova, E. Jasinskaja. Hermito kvadrikų lygčių invariantai neeuklidinėse ir semineeuklidinėse unitarinėse erdvėse